Evaluation of bowel wall thickness by ultrasound as early diagnostic tool for therapeutic response in Crohn’s disease patients treated with ustekinumab - Hoffmann, Tatjana; Fusco, Stefano; Blumenstock, Gunnar; Sadik, Saman; Malek, Nisar P; Froehlich, Eckhart (Zeitschrift für Gastroenterologie, 2020)
Background Ustekinumab was approved for the treatment of patients with moderate to severe CD 2. Development of predictors for selecting patients responding to ustekinumab has to be the next step. US offers a noninvasive method with great sensitivity in detecting CD activity 11.Aim To evaluate BWT by BS as early diagnostic tool for treatment response in CD patients treated with ustekinumab at week 8.Methods This is a prospective monocentric study. Twenty-three CD patients had BS at the time of first and second application. BS was performed by one of 2 experienced DEGUM certificated sonographers, with evaluation by both independently and blindly. Primary endpoint was substantial sonographic response defined as decrease of BWT ≥ 1 mm. Secondary endpoint was concordance between sonographic and clinical response, defined as decrease of CDAI ≥ 70 points and sonographic and biochemical response defined as decrease of CRP ≥ 0.5 mg/dl.Results At week 8, BS detected in 10 of 23 patients a substantial decrease of BWT ≥ 1 mm; in 7, a decrease < 1 mm. Compared to baseline, all 17 patients showed generally improved blood data and 16/17 generally improved clinical data. Of those with a decrease of BWT ≥ 1 mm, we observed a substantial decrease of CDAI ≥ 70 points in 9/10 patients and a substantial decrease of CRP ≥ 0.5 mg/dl in 8/10 patients.Conclusion Our study suggests that sonographic measurement of BWT can be a helpful parameter for selecting patients responding early to ustekinumab and for providing assistance in terms of further treatment interval at week 8.
Keywords: ustekinumab; Crohn’s disease (CD); bowel sonography (BS)